Protein-polysaccharide nanoconjugates: Potential tools for delivery of plant-derived nutraceuticals - Paliya, Balwant S.; Sharma, Vivek K.; Sharma, Minaxi; Diwan, Deepti; Nguyen, Quang D.; Aminabhavi, Tejraj M.; Rajauria, Gaurav; Singh, Brahma N.; Gupta, Vijai Kumar (Food chemistry, 2023)
[Display omitted] •Natural proteins and polysaccharides as nanocarries were summarized.•Bioavailability of protein-polysaccharide nanoconjugates were discussed in details.•Advantages of these nanoconjugates for encapsulation were summarized.•The possible research gap, challenges and future perspectives were discussed. Protein-polysaccharide nanoconjugates are covalently interactive networks that are currently the subject of intense research owing to their emerging applications in the food nanotechnology field. Due to their biocompatibility and biodegradability properties, they have played a significant role as wall materials for the formation of various nanostructures to encapsulate nutraceuticals. The food-grade protein-polysaccharide nanoconjugates would be employed to enhance the delivery and stability of nutraceuticals for their real use in the food industry. The most common edible polysaccharides (cellulose, chitosan, pectin, starch, carrageenan, fucoidan, mannan, glucomannan, and arabic gum) and proteins (silk fibroin, collagen, gelatin, soy protein, corn zein, and wheat gluten) have been used as potential building blocks in nano-encapsulation systems because of their excellent physicochemical properties. This article broadens the discussion of food-grade proteins and polysaccharides as nano-encapsulation biomaterials and their fabrication methods, along with a review of the applications of protein-polysaccharide nanoconjugates in the delivery of plant-derived nutraceuticals.